Social media proficiency, digital information accessibility and information sharing behaviors among library and information science students - Wada, Ibrahim; Madu, Augustine Uzoma; Joel, Anthonia Peace (Record and Library Journal, 2023)
Background of the study: Students proficiency in using academic resources is a topic of interest, particularly in social media utilisation, digital information literacy, and online information sharing practices. Purpose: The study investigated the social media proficiency, digital information accessibility and information sharing behaviours among library and information science students, university of Maiduguri, Borno State Method: The study was guided by 3 research objectives and 2 hypotheses. The study consisted 742 undergraduate students, out of which 649 responded to the questionnaire dispersed through online survey. Mean scores and standard deviations were used for descriptive analysis and inferences were made with regression analysis. Findings: Students demonstrated moderate digital literacy skills for academic activities, with average competencies in locating and evaluating quality online sources and leveraging digital tools, (xÌ…w = 3.01, Std. 1.489); and that social media usage among the students is moderately frequent (xÌ…w= 2.97, Std.= 1.48); while collaborative digital learning behaviours are moderately high among the LIS students (xÌ…w = 3.68, Std. = 1.435). Conclusion: Individual student engaged in online collaboration and communication via social media for educational purposes, but still have deficiencies in certain abilities such as evaluating online authenticity, and effectively managing distractions.